2016
DOI: 10.1159/000446480
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Migration of Peripheral Retinal Pigment Epithelial Cells Are Associated with the Upregulation of Wingless-Related Integration and Bone Morphogenetic Protein Signaling in Dark Agouti Rats

Abstract: Objective: The aim of this study was to investigate the possible migration of proliferating peripheral retinal pigment epithelial (RPE) cells and their association with differential gene expressions. Materials and Methods: The RPE layer was obtained from the inner aspect of the eyeball of dark agouti rats (12-13 weeks old) and was mounted on glass slides. The peripheral RPE cell proliferation was evaluated using bromodeoxyuridine immunohistochemistry (n = 10). The cell migration was examined using the Dil trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…They are not only the main forces of blood–retina barrier, but also centrally involved in the pathogenesis of retinal disorders 65 , 66 . CD44 is overexpressed in the surface of RPE and hence can be used as a key target for a number of drugs and gene-based therapeutics 67 , 68 . In Martens׳s work, a nonviral polymeric gene complex with hyaluronic acid (HA) coating was demonstrated and shown to be efficiently taken up by RPE cells via the CD44-receptor mediated endocytosis, resulting in a high gene delivery and expression of green fluorescent protein (GFP) in the eye 69 .…”
Section: Nanosystems For Ocular Posterior Disease Therapymentioning
confidence: 99%
“…They are not only the main forces of blood–retina barrier, but also centrally involved in the pathogenesis of retinal disorders 65 , 66 . CD44 is overexpressed in the surface of RPE and hence can be used as a key target for a number of drugs and gene-based therapeutics 67 , 68 . In Martens׳s work, a nonviral polymeric gene complex with hyaluronic acid (HA) coating was demonstrated and shown to be efficiently taken up by RPE cells via the CD44-receptor mediated endocytosis, resulting in a high gene delivery and expression of green fluorescent protein (GFP) in the eye 69 .…”
Section: Nanosystems For Ocular Posterior Disease Therapymentioning
confidence: 99%
“…Enrichment analysis showed that their target genes were classified into several pigmentation-related pathways, including the Wnt signaling pathway, the MAPK (mitogen-activated protein kinase) signaling pathway, and melanogenesis ( Figure 6 ; Supplementary Table S5 ). Among the targets, mc1r , the most important regulator of melanogenesis, positively regulated cyclic AMP (cAMP) response-element binding protein ( creb ) and downstream mitf to increase melanin synthesis [ 29 ]; wnt4 was also reported to be maintained at higher levels in normal peripheral retinal pigment epithelium cells in dark agouti rats [ 30 ]. In normal melanocytes, the activation of Mc1r-cAMP-Mift pigmentation signaling cascade has been proved to induce the production of transforming growth factor (TGF)-β1 in transformed melanocytes in human melanoma cells and play crucial roles in ultraviolet (UV) light exposure-induced skin pigmentation [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing cell divisions, apoptosis and cell mingling make the epithelia a highly dynamic place (Al-Hussaini et al 2016;Christ et al 1990;Gardner 1986;Macara et al 2014). Interestingly, monolayer stress profiles of such epithelial layers reveal dynamic heterogeneity, with intercellular stress displaying stochasticity in space and time, meaning that stress is tied neither to any particular position nor to any particular cell within the monolayer (Angelini et al 2010(Angelini et al , 2011Garrahan 2011;Tambe et al 2011).…”
Section: Jamming Transition and Dynamic Heterogeneitymentioning
confidence: 99%
“…Epithelial cells construct inner and outer linings of our organs and function as physical barriers, thus, protecting the underlying tissue from infections, dehydration, and also aiding in efficient absorption of nutrients and gases (Alberts 2008). Cells within the epithelia perform these tasks, being jammed at their place while also making sure that epithelial homeostasis is maintained, failing in which can be potentially fatal for the tissue (Macara et al 2014).…”
mentioning
confidence: 99%